2023
DOI: 10.1093/ageing/afad154
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative interventions to improve early mobilisation and physical function after hip fracture: a systematic review and meta-analysis

Mitchell N Sarkies,
Luke Testa,
Ann Carrigan
et al.

Abstract: Background Perioperative interventions could enhance early mobilisation and physical function after hip fracture surgery. Objective Determine the effectiveness of perioperative interventions on early mobilisation and physical function after hip fracture. Methods Ovid MEDLINE, CINAHL, Embase, Scopus and Web of Science were searched from January 2000 to March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…A review conducted by Sarkies et al., found other peri‐operative factors which could further influence early mobilisation (Sarkies et al., 2023). They identified that use of peripheral nerve blocks and TENS analgesia therapies could reduce reliance to opioids and thus reduce side effects such as confusion, nausea, and haemodynamic instability (Sarkies et al., 2023). Furthermore, liaison with orthogeriatric services optimises management of co‐morbidities and thus optimises medically stability, reducing complications (Sarkies et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A review conducted by Sarkies et al., found other peri‐operative factors which could further influence early mobilisation (Sarkies et al., 2023). They identified that use of peripheral nerve blocks and TENS analgesia therapies could reduce reliance to opioids and thus reduce side effects such as confusion, nausea, and haemodynamic instability (Sarkies et al., 2023). Furthermore, liaison with orthogeriatric services optimises management of co‐morbidities and thus optimises medically stability, reducing complications (Sarkies et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…They identified that use of peripheral nerve blocks and TENS analgesia therapies could reduce reliance to opioids and thus reduce side effects such as confusion, nausea, and haemodynamic instability (Sarkies et al., 2023). Furthermore, liaison with orthogeriatric services optimises management of co‐morbidities and thus optimises medically stability, reducing complications (Sarkies et al., 2023). They also highlighted that delays in hip fracture surgery leads to poorer outcomes (Sarkies et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations